Identity Politics Violations in Indonesian Elections - Suhariyanto, Didik (Green Publisher Indonesia, 2024)
Identity politics violations are a frequent phenomenon in elections in Indonesia, where ethnic, religious, ethnic, gender, or other social group identities are manipulated or exploited for political gain. The purpose of this study is to identify, analyze, and understand more deeply about identity politics violations in elections, as well as their implications for democracy and Indonesian society as a whole. The analysis will be based on the theory of identity politics, multiculturalism, and political participation. The results of the analysis show that political elites and candidates for regional heads tend to use or maintain identity politics for political interests and strengthen power hegemony. As a result, the use of religious issues as political tools in the 2019 Presidential Election is a source of tension and a potential threat to the country's social and political stability. With a deeper understanding of this phenomenon, this research is expected to provide valuable insights for political stakeholders, electoral institutions, and society at large to develop prevention and countermeasures against identity politics violation and strengthen the foundation of an inclusive and equitable democracy in Indonesia.